Adolescent Pregnancy's Ongoing Effects on the Depression and Anxiety Scores in Subsequent Pregnancy - Esengul Turkyilmaz; Selma Tural Hesapcioglu (Medical Network, 2019)
Objective: Child/adolescent 'marriages' and following pregnancies have adverse effects both on the child and adolescent mother. The aim of this study is to detect whether the adult pregnant women who have previous adolescent pregnancy more susceptible to the depression and anxiety than current adolescent pregnants and the adult pregnant women who have no adolescent pregnancy history. Study Design: This cross sectional study evaluated a total of 163 pregnant women who attended to our antenatal clinic. Subjects aged between 16 and 43 years including both adolescent and adult pregnant women were divided into three groups. These groups are current adolescent pregnant women (Group I), adult pregnant women who have adolescent pregnancy history (Group II), adult pregnant women who have no adolescent pregnancy history (Group III). Three groups were compared in terms of the pregnancy status, socio-demographic variables and depression-anxiety scores. Result: In the current study the highest depression and anxiety scores were observed in Group II [depression scores' median (IQR) values respectively 5 (8.5) points for Group I, 12.5 (8.5) for Group II, 9 (12) for Group III (p<0.001 between Group I and Group II for BDI comparison). Anxiety scores' median (IQR) values respectively 19.5 (15.5) for group II, 9 (15.5) for group I, 14 (15.25) for Group III (p=0.005 between Group I and Group II for BAI comparison). Conclusion: Marriage and pregnancy at an early age are considered as risk factors for psychiatric morbidity in the next pregnancy. Therefore, women with a history of teenage pregnancy should be carefully monitored for depression and anxiety symptoms.